Stakeholder Pressure and Ownership Structure on Sustainability Report Disclosure : Tekanan Pemangku Kepentingan dan Struktur Kepemilikan terhadap Pengungkapan Laporan Keberlanjutan - Rina Tjandrakirana DP; Ermadiani Ermadiani; Apriyansyah Apriyansyah; Alditya Aris Rinandy; Zahwa Aliyah (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Global attention to sustainability has increased significantly, urging companies to integrate social and environmental accountability into business practices through sustainability reports. Specific background: In Indonesia, regulations such as POJK No. 51/POJK.03/2017 have strengthened the disclosure of Environmental, Social, and Governance (ESG) information, particularly in energy sector firms with high environmental impacts. Knowledge gap: However, prior studies reveal inconsistent findings regarding how stakeholder pressure and ownership structure influence the extent of sustainability report disclosure. Aims: This study examines the effects of stakeholder pressure—measured by investor orientation and external audit pressure—and foreign ownership structure on the level of sustainability report disclosure among energy companies listed on the Indonesia Stock Exchange during 2021–2023. Results: Using panel data regression on 18 companies (54 observations), the findings show that investor and audit pressures have no significant effects, while foreign ownership positively influences disclosure at the 10% level (β = 0.177; p = 0.054). Novelty: The study highlights that foreign investors play a critical role in enhancing sustainability transparency in emerging markets. Implications: Strengthening domestic investor awareness and external audit roles is essential to improving sustainability reporting quality and aligning Indonesia’s corporate practices with international ESG standards. Highlights: Foreign ownership significantly enhances sustainability report transparency. Investor and audit pressures show no significant effect in Indonesia’s energy firms. Findings emphasize the need to strengthen domestic ESG engagement and governance. Keywords: Stakeholder Pressure, Foreign Ownership, Sustainability Report, Esg Disclosure, Audit Quality